COMPUTER METHOD OF CONTROL OF KNOWLEDGE OF STUDENTS OF GENERAL TECHNICAL DISCIPLINES - Antonenko І.І.; Tsis О.О. (Pedagogy of Higher and Secondary Education, 2022)
As a result of research the made to order computer method of control of knowledges of students of technical disciplines on the base of the program "Assistant" with electronic educational part of course of lectures in text editor Microcoft Word.